Pengaruh Kebijakan Dividen Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Sub Sektor Makanan Dan Minuman Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024 - Fadila Rahmadani Safitri; Berta Agus Petra; Nila Pratiwi (CV. ITTC INDONESIA, 2026)
This study aims to determine the effect of dividend policy and capital structure on firm value, with profitability as an intervening variable, in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The population in this study was all 42 food and beverage sub-sector companies listed on the IDX during the study period. The sampling technique used a purposive sampling method to obtain a sample of 22 companies with an observation period of five years. The data analysis method used was multiple linear regression analysis and path analysis with the help of the SPSS 26 program. Based on the results of hypothesis testing, the results showed that capital structure had a significant effect on profitability, while dividend policy did not have a significant effect on profitability. Dividend policy had a significant effect on firm value, while capital structure did not have a significant effect on firm value. Profitability had a significant effect on firm value. The path analysis showed that dividend policy did not have a significant effect on firm value through profitability, and capital structure also did not have a significant effect on firm value through profitability in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2024 period.